Development of grape pulp enriched low calorie ice cream made with aspartame and maltodextrin - Reddy, Yemereddy Kotilinga; Palla, Sasikala; Rao, K Nageswara; Reddy, G Vijaya Bhaskar (Indian Journal of Dairy Science, 2023)
An attempt has been made to increase anti-oxidants present at higher levels in grape pulp by incorporating in ice cream to enhance the functional properties and nutritional quality. Ice cream was prepared using grape pulp at 8 to 12% levels in ice cream mix prior to freezing. Inclusion of grape pulp at augmented levels resulted in significant changes in physico-chemical properties and antioxidant activity of ice cream. The total solids content was decreased on addition of grape pulp in ice cream at increasing levels.Â The functional constituents i.e. antioxidant activity increased with greater level of inclusion. Incorporation of grape pulp raised the melting resistance of ice cream and decreased overrun. The samples with 10% grape pulp incorporated low calorie ice cream was found to have highest overall acceptability scores with enhanced functional properties and nutritional value.Â